Aspectos Morfologicos e Histoquimicos de los Musculos Extraoculares del Zorrillo (Didelphis albiventris) - Matheus, S. M M [UNESP]; Soares, J. C. [UNESP]; Neves Da Silva, A. M. [UNESP] (Blackwell Wissenschafts Verlag Gmbh, 1997)
The extraocular muscle fibres of the South-American opossum were determined according to their metabolic profiles using NADH-diaforase, and myofibrilar ATPase after pre-incubation in both acid (pH 4.3) and alkaline (pH 10.4) media. Three muscles were selected to study the arrangement of the fibres (obliquous dorsalis, rectus dorsalis and rectus lateralis muscles). It was demonstrated that they are organized in two layers: the orbital layer composed by small diameter fibres and the global layer with three-times thicker fibres than the former. The global layer has three fibre types: white, red and intermediate; while the orbital layer presents two fibre types, which react differently to the ATPase.
Morphological and histochemical aspects of the extraocular muscles of the South-American opossum (Didelphis-albiventris)
Keywords: Adenosine triphosphatase; Dihydrolipoamide dehydrogenase; Animal; Chemistry; Cytochemistry; Eye; Histology; Male; Opossum; Orbit; Skeletal muscle; Adenosine Triphosphatases; Animals; Dihydrolipoamide Dehydrogenase; Eye; Histocytochemistry; Male; Muscle, Skeletal; Opossums; Orbit